COMPREHENSIVE ASSESSMENT OF ESTROGENIC CONTAMINATION OF SURFACE WATERS OF THE RIVER BASIN SUQUIA - Gallardo Gustavo; Ferral Alberto; Alaniz Eugenia; Ferral Anabella; Sarmiento Tagle Martin; Vanesa Crissi Aloranti (European Scientific Journal, ESJ, 2014)
Estrogenic compounds are a class of pharmaceutical products harmful to the animals and a cause of environmental damage. The biological activity of these compounds is high, which are designed to operate at low concentrations. Therefore, even in low concentrations in the environment can have harmful effects on aquatic organisms and in humans, who might be consuming water or food contaminated with estrogen. The generic term (estrogen) applies to any substance, natural or synthetic exert biological effects characteristic of ovarian estrogenic hormones, many anabolic and growth promoters in animals, which has led to its misuse in the commercial animal. Estrogen produced in the laboratory can be used as a type of birth control and the treatment of menopausal symptoms, menstrual disorders, osteoporosis and other health treatment. There are three main forms of estrogen found in the human body, Estrone (E1), 17 betaestradiol (E2) and estriol (E3). Estrone (E1) is the most common estrogen in greater quantities in postmenopausal women. Over the last decades, residues of hormones E1, E2 and E3, have been reported mainly in river water and sediments due to the inevitable link to WWTP effluents discharging into the receiving waters In this brief review, we provide an overview of sources, environmental concentrations in surface and ground water, and summarize the current knowledge on fate and behavior of these steroid compounds. And we describe the first sampling campaign (surveys and water samples of the Suquia River) and we present a brief analysis of the surveys.